1971
DOI: 10.1111/j.1479-828x.1971.tb00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Endocarditis in Pregnancy

Abstract: Five cases of bacterial endocarditis associated with pregnancy are described. Despite modem therapy, the seriousness of the condition prevails. Emergency vaIve replacement during the acute stage of the disease is now possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1
2

Year Published

1976
1976
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 8 publications
0
19
1
2
Order By: Relevance
“…Studies have reported rates of GBS colonization in pregnant women of 4.6% to 40.6% [1, 4, 5]. Fifty percent of colonized mothers transmit GBS to their newborns [1].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported rates of GBS colonization in pregnant women of 4.6% to 40.6% [1, 4, 5]. Fifty percent of colonized mothers transmit GBS to their newborns [1].…”
Section: Discussionmentioning
confidence: 99%
“…Infective endocarditis (IE) in pregnancy is a rare and life-threatening condition with a reported incidence of 0.006% and a maternal mortality rate of 15–20% 1 2. Reports suggest that IVDU is becoming a more common risk factor for infective endocarditis in pregnancy,3 and now accounts for up to 14% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Jinekolojik ve doğum işlemleri sonrasında infektif endokardit gelişme riski düşüktür 0.03-0.14/1000 doğum (4,5). Dahası elektif abortusda infektif endokardit sıklığının çok daha düşük olacağı tahmin edilmektedir 0.001/1000 doğum (4).…”
Section: Discussionunclassified